Improved capacity for influenza surveillance in the WHO Eastern Mediterranean Region: Progress in a challenging setting. Issue 3 (March 2020) - Malik, Mamunur R.; Abubakar, Abdinasir; Kholy, Amgad E.; Buliva, Evans; Khan, Wasiq M.; Lamichhane, Jaya; Moen, Ann; McCarron, Margaret; Zureick, Kinda; Obtel, Majdouline
Abstract: Background: The World Health Organization Regional Office for Eastern Mediterranean has partnered with the United States Centers for Disease Control and Prevention (CDC) to strengthen pandemic influenza preparedness and response in the Region since 2006. This partnership focuses on pandemic preparedness planning, establishing and enhancing influenza surveillance systems, improving laboratory capacity for detection of influenza viruses, estimating the influenza disease burden, and providing evidence to support policies for the introduction and increased use of seasonal influenza vaccines. Methods: Various published and unpublished data from public and WHO sources, programme indicators of the CDC cooperative agreement and Pandemic Influenza Preparedness Framework were reviewed and analysed. Analyses and review of the programme indicators and published articles enabled us to generate information that was unavailable from only WHO sources. Results: Most (19/22) countries of the Region have established influenza surveillance system; 16 countries in the Region have designated National Influenza Centres. The Region has seen considerable improvement in geographic coverage of influenza surveillance and influenza detection. Virus sharing has improved and almost all of the participating laboratories have achieved a 100% efficiency score in the WHO external quality assessment programme. At least seven countries have estimated their influenza disease burden using surveillance data and at least 17 are now using seasonal influenza vaccines as a control strategy for influenza illness. Conclusion: The Region has achieved substantial progress in surveillance and response to seasonal influenza, despite the adverse effects to the health systems of many countries due to acute and protracted emergencies and other significant challenges.